Растениеобитающие клещи-фитосейиды Черноморского заповедника с описанием двух новых видов рода Ambhjseius - Колодочка, Л.А.; Бондаренко, Л.В. (Вестник зоологии, 1993)
Two species are described as new: Amblyseius argillaceus sp. n., and A. fragilis sp. n. from the Kherson Region of the Ukraine. The list of 38 species of the 8 genera of phytoseiid mites of the reserve is given together with names of plants on which they were found. Distribution and mite-plant connections are discussed